RABIES INFECTION AND CONTROL IN THE EASTERN UNITED STATES - Lux, Hannah (My University, 2019)
Anne Arundel County Animal Care & Control (AACACC) is a Maryland county department that works to maintain safe human-animal interactions and promotes the humane treatment of animals. The Bite Investigation Department, where I primarily worked, investigates domestic and wild animal bites, conducts rabies surveillance, and serves warning letters and citations to potentially dangerous and dangerous animals. Rabies is a zoonotic virus from the genus Lyssavirus and poses a significant public health concern both worldwide and in the United States (1–3). While the United States has been canine-rabies free since 2007, there are multiple variants maintained in wild mammalian reservoirs, most importantly in raccoons (Procyon lotor) and eastern pipistrelle bats on the eastern coast of the United States (2, 4–10). While working with the Bite Investigation Department at AACACC, my learning objectives were broadly to gain experience working in a county department. More specifically, my goals were to complete data entry and analysis of the major aspects of the Bite Investigation Department. Additionally, I was able to have a ride-along with an Animal Care & Control Officer (ACCO), go to animal abuse court hearings, and attend webinars. I created many products that satisfy the six MPH foundational competencies and two MPH infectious diseases/zoonoses competencies. These products included spreadsheets containing data from rabies surveillance and warning letters, potentially dangerous orders, and dangerous orders, graphs that analysis these data, brochures, and templates for data collection.
Keywords: rabies; Anne Arundel County; Eastern United States; Animal Care and Control; ORV; Raccoons